2004
DOI: 10.1111/j.1365-246x.2004.02431.x
|View full text |Cite
|
Sign up to set email alerts
|

A magnetoclimatological investigation of Pampean loess, Argentina

Abstract: S U M M A R YMagnetic susceptibility has proved to be a very useful tool for understanding Northern Hemisphere loess/palaeosol sequences, both for intersite correlation and for broad climatic interpretation. However, there are two competing magnetoclimatological models that predict completely opposite patterns of variability-the so-called wind-vigour and pedogenic models. In the former, stronger winds during glacial intervals entrain larger quantities of dense magnetic particles than during interglacials. Glac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 18 publications
(21 reference statements)
5
24
0
9
Order By: Relevance
“…Several studies have shown that pedogenetic processes may not only explain high MS values like in the Chinese loesspalaeosol sequences, but also may be associated with low MS values (Rousseau et al, 2002;Feng and Khosbayar, 2004;Bidegain et al, 2005). This inverse pattern is mainly attributed to the process of "gleying" and the coinciding destruction of magnetic minerals in water logged soils.…”
Section: Magnetic Susceptibilitymentioning
confidence: 90%
“…Several studies have shown that pedogenetic processes may not only explain high MS values like in the Chinese loesspalaeosol sequences, but also may be associated with low MS values (Rousseau et al, 2002;Feng and Khosbayar, 2004;Bidegain et al, 2005). This inverse pattern is mainly attributed to the process of "gleying" and the coinciding destruction of magnetic minerals in water logged soils.…”
Section: Magnetic Susceptibilitymentioning
confidence: 90%
“…According to the measurements of rock magnetic parameters carried out in soils horizons, the mode of magnetic pattern around 38°S indicates that susceptibility values increase upwards in the soils profiles. The opposite has been mentioned in La Plata area in [6], giving rise to the idea that the rainfall may control the magnetic signal.…”
Section: Introductionmentioning
confidence: 90%
“…Bidegain et al [6] mention the existence of a third magneto-climatic model for the Argentine loess deposits that differ from the wind vigor model (prevailing in Siberian soils) and the pedogenetic model (widespread in the Chinese sequences). In the Argentine case, the western winds during glacial intervals entrain large quantities of dense magnetic particles than during interglacial periods.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Зміни петромагніт-них характеристик з глибиною в цьому випадку не відо-бражають літологію розрізу: як лесові товщі, так і вико-пні ґрунти характеризуються і підвищеними, і знижени-ми значеннями магнітної сприйнятливості (та деяких інших магнітних параметрів). До такого типу, з відсутні-стю закономірностей у змінах магнітних властивостей, відносять відклади Польщі, Західної України [12; 15], Аргентини [5], Пакистану [4,[15][16].…”
Section: рис 2 магнітні характеристики відкладів розрізу коршівunclassified